“You are a TERF”: Discursive-semantic analysis of the use of the acronyms TERF and TRA in the trans-inclusive and trans-exclusionary radical feminism conflict - Inés de la Villa Vecilla (Asociación de Jóvenes Lingüistas, 2021)
The present study investigates the motives and intricacies of the conflict between the trans-inclusive and trans-exclusionary communities from a linguistic perspective. The purpose of the study is to analyse the use and the connotations of the acronyms TERF and TRA across the two groups, as well as examining the representation of participants in USA-based forums regarding this matter. In order to tackle this issue, this paper uses WordSmith Tools to carry out a discursive-semantic analysis of the conflict and the acronyms TERF and TRA. Employing a mixed- method approach, quantitative analysis revealed that the use of these acronyms is higher in trans- exclusionary forums. Moreover, findings from the qualitative analysis shed light on the conceptualization of the conflict as a war through metaphors, and the representation of participants as enemies in the two groups. In summary, different discursive and linguistic strategies are employed in trans-inclusive and trans-exclusionary forums that perpetuate and enhance the online conflict.